PENINGKATAN PROFESIONALITAS PENGAJAR AGAMA DI ERA DIGITAL MENYONGSONG REVOLUSI 4.0 (Suatu Tinjauan PAK dalam Perspektif Pedagogik Kritis) - Wem. David. Rindengan (Institut Agama Kristen Negeri (IAKN) Ambon, 2019)
This paper is a critique of the traditional pedagogic in education using the critical pedagogic concept formulated by George. S. Counts. Critical pedagogic seeks to view the need for a new social society that can cope with various distributions and regulatory needs through education. In the educational world the teacher's role in the school is an active cultural bearer instead of teaching a passive culture. In the context of religious teachers in this regard, will deal with methods of educating that must conform to the development of science and technology. Teacher/lecturer is the creator of the learning process is required to further improve professionalism so as to create a learning society that thinks past the boundaries of kinship, thinking to create a better future. A critical pedagogic concept formulated by George. S. Counts, referred to as